Chairside fabrication of customized healing abutment by socket impression in immediate implantation. Case report - Aleksandar Naydenov; Yanita Slavcheva; Milica Dzhambazova; Ivet Dzhondrova; Anton Tumbalov; Ilia Liondev (Problems of Dental Medicine, 2026)
Background: Customized healing abutments may support the peri-implant mucosa after immediate implant placement, but many available workflows require direct intraoral resin application, computer-aided design and manufacturing, or laboratory support. Case description: A 28-year-old systemically healthy man presented with a non-restorable mandibular left first molar (FDI tooth 36). After atraumatic extraction and guided Type 1 implant placement, an addition-silicone socket impression was made around a temporary abutment. The impression was trimmed extraorally and used as a scaffold for a flowable and paste composite shell. The finished and polished component was a non-loaded customized healing abutment. At the 1-week review, clinical inspection showed stable soft-tissue adaptation and minimal inflammation. Following the planned healing period, a definitive zirconia crown was delivered. At 6 months after implant placement, the peri-implant mucosa remained clinically stable without visible recession. At 12 months panoramic radiographic section showed preserved peri-implant crestal bone without evident marginal bone loss. These follow-up findings were qualitative. Standardized soft-tissue measurements and calibrated baseline periapical radiographs were not presented. Conclusion: This report describes an direct-indirect, laboratory free chairside method that transfers the socket contour to a composite healing abutment while allowing resin application, finishing, and polishing outside the oral cavity. Stable clinical and radiographic conditions were observed at 6 and 12 months in this patient. However, the single-case design and absence of quantitative measurements preclude conclusions regarding comparative effectiveness or general predictability.